6x-8-(9x-1)=x-6

Simple and best practice solution for 6x-8-(9x-1)=x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-8-(9x-1)=x-6 equation:


Simplifying
6x + -8 + -1(9x + -1) = x + -6

Reorder the terms:
6x + -8 + -1(-1 + 9x) = x + -6
6x + -8 + (-1 * -1 + 9x * -1) = x + -6
6x + -8 + (1 + -9x) = x + -6

Reorder the terms:
-8 + 1 + 6x + -9x = x + -6

Combine like terms: -8 + 1 = -7
-7 + 6x + -9x = x + -6

Combine like terms: 6x + -9x = -3x
-7 + -3x = x + -6

Reorder the terms:
-7 + -3x = -6 + x

Solving
-7 + -3x = -6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-7 + -3x + -1x = -6 + x + -1x

Combine like terms: -3x + -1x = -4x
-7 + -4x = -6 + x + -1x

Combine like terms: x + -1x = 0
-7 + -4x = -6 + 0
-7 + -4x = -6

Add '7' to each side of the equation.
-7 + 7 + -4x = -6 + 7

Combine like terms: -7 + 7 = 0
0 + -4x = -6 + 7
-4x = -6 + 7

Combine like terms: -6 + 7 = 1
-4x = 1

Divide each side by '-4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| (-15/8)/(45/2) | | 36x+31=1+6x | | 8+8n=4(4n-7)-4 | | Y=x^4-x^2+3 | | T=C+qm | | y+3=2x+3 | | 23*7-45= | | 3/10x40 | | -x=-37/8 | | 71/5 | | 2x+9y=70 | | 6+2x-7x=9 | | 9x+48=6x-12 | | 6Y=20-5X | | 6r-10=-4+7r | | (5/14)÷(2/7) | | 8v+39=-3v-7(8+4) | | 4x^2-15x-x=0 | | x^4(1/9x^3)(6x^4 | | 8xsquared+18x+10=0 | | 6x+5x=17 | | 5*3+2*5= | | (7x+4)*(-4x-5)= | | 3/10×40 | | 1/2b=-3 | | 4y+1=y-3 | | 10x^2+20x-150=0 | | 20/7n-5/3n | | 10x+2y=7 | | 21=7/8x | | 7(-x-4)=-2x-33 | | p-7.2=-3.43 |

Equations solver categories